Observation of three different linker conformers in a scandium ferrocenedicarboxylate coordination polymer. Issue 34 (17th August 2020) - Benecke, Jannik; Svensson Grape, Erik; Engesser, Tobias A.; Inge, A. Ken; Reinsch, Helge
Abstract : In the coordination polymer CAU-50 based on 1, 1′-ferrocenedicarboxylate and scandium, three different conformers of the same linker molecule are observed. Abstract : Electron and powder diffraction were combined to elucidate the structure of the new coordination polymer [Sc2 (FcDC)3 ] based on 1, 1′-ferrocenedicarboxylate (FcDC 2− ), denoted as CAU-50. Remarkably, three different conformers of the very same linker molecule are observed, two of which serve as connectors for the scandium cations while one conformer acts as capping agent.